Research - Hungarian Institute for Public Opinion Research
The sub-fonds contains a single series, 420-1-1, documents on public opinion and media research. Although the Institute’s public opinion and media research activities were not necessarily interconnected, as its research profile took shape, the distinction between these two areas gradually became harder to define, since surveys were carried out simultaneously. The series also includes studies on various cultural communications topics, such as rumors and how they spread, the public’s knowledge of foreign languages, the sociology of free time, public perceptions of official celebrations and their presence in everyday life, visual culture, how people used their mother tongue and functional illiteracy, ways in which the Chernobyl nuclear power plant disaster was understood in Hungarian media and public opinion, and, as a precursor to the change of system, public perceptions of the 1956 uprising. At the time of its founding, the Institute’s main profile concerned media research, which played a defining role in its activities until the end. Although this part of the collection does not contain background materials to the various contents analyses, the secondary literature indicates that the majority of contents analyses—which became increasingly important in the Institute’s work—aimed at tracing the formation of the economic mood in the country in tandem with systematic analysis of the media’s coverage of economic issues. Tendencies captured by mass media announcements on the economy (‘success story’ propaganda, omissions and distortions) were analyzed, as were the relations and interconnections between such media reports and public opinion. At the same time, numerous targeted surveys were carried out using contents analysis into specific media programs (series, contests, and discussion shows) or specific phenomena (including women in the media, the representation of Austrians in the press, and music programs), in order to explore their contents and visual characteristics. Research into mother tongue usage focused on reading skills, comprehension and functional illiteracy. In panel surveys, the Institute also measured levels of foreign language knowledge a number of times per year, while other research projects analyzed the visual characteristics of media content. Throughout the period of its existence, the Institute paid careful attention to the methodological basis of empirical research. Methodological research dealt primarily with technical and contents problems related to survey method, such as the context of questionnaires, problems in formulating questions, and the order sequence of questions. Some research projects tried to ascertain the possible motivations behind ‘don’t know’ responses, while others attempted to reach exact measurements of viewership and listenership figures. Our present practice of handling these various types of research together reflects the fact that the Institute’s researchers endeavored, from the beginning, to observe and analyze social communication processes, how means of mass communication functioned, changes in the culture of communication and the formation of public perceptions, as well as the mutual influence between these phenomena, as a systemic whole. The Institute’s research methodology placed great emphasis on utilizing the greatest variety of disciplines and methodologies in examining communication phenomena. In terms of the constitution of its researchers and data gatherers, the Institute also strove to emphasize interdisciplinarity. Among its employees were economists, humanities scholars, psychologists, philosophers, lawyers and mathematicians; a good few more arrived with qualifications in the natural sciences, alongside art historians, theoretical linguists and even special needs teachers. From the research documentation, only the duplicate copies of foldouts containing raw data were destroyed. OSA has successfully preserved 88% of the data files, and processed 200 to date; work on the remainder is in progress. Accruals expected